Majoon chobchini reinstates PDL-1 expression and blocks dendritic cell -T helper 17 pathogenic axis in rheumatoid arthritis animal model. (March 2023) - Samarpita, Snigdha; Rasool, Mahaboobkhan
Abstract: Dendritic cells (DCs) are the critical players in the puzzle of rheumatoid arthritis (RA) disease pathogenesis. Blockade of DC activation has been shown to curtail Th17 cell differentiation and its aberrant function in RA. Recent studies have pointed to the role of the PI3K/AKT signaling axis in the maturation and activation of DCs. However, it is yet to be established how PI3K/AKT inhibition would lead to the abolishment of DC activation and Th17 cell plasticity in RA. Herein, our study decoded whether and how majoon chobchini, an unani compound, abated dendritic cell maturation and regulated the Th17/Treg paradigm in RA. Given our results, majoon chobchini conspicuously restrained MHC II, CD86 expression and, subsequently elevated PDL-1 levels in DCs in-vivo. Of note, inhibition of DC maturation by majoon chobchini, in turn, favoured suppression of the Th17 cell population while driving Treg cell development in adjuvant induced arthritic (AA) rats. Concurrently, majoon chobchini decreased the catabolic effects of IL-17 (Th17 associated cytokine) via a reciprocal increase in IL-10 (Treg associated cytokine) levels in AA rats. Mechanistically, majoon chobchini sustained FoxO1 nuclear localization signaled through dampened PI3K/AKT phosphorylation in-vitro. In concert, PDL-1 expression was heightened in majoon chobchini treated activated DCs that provides a framework for ablation of the DC-Th17 cell pathogenic axis in RA. Notwithstanding, the PI3K inhibitor LY294002 exhibited similar inhibitory effects. In essence, majoon chobchini enhanced PDL-1 expression that abolished DC maturation via regulation of the PI3K/AKT/FoxO1 axis, thereby hindering Th17 differentiation in an animal model of RA. This further warrants a clinical investigation that could validate majoon chobchini as a prospective therapeutic drug in the treatment of RA.